The use of comic strips as pre-reading activity to improve reading comprehension of narrative text for year 3 pupils / Nor Asmahani Hassim - Hassim, Nor Asmahani (Faculty of Education, 2015)
The Year 3 pupils of Sekolah Kebangsaan Batu 9 Jalan Bomba, Tanjung Karang lack motivation in reading English materials. Something needs to be done to improve their reading readiness. The purpose of this study was to examine the usefulness of comic strips in the prereading activity within the lesson which could improve the Year 3 pupils' reading comprehension of narrative text. The study was conducted on 30 pupils from class 3 Cerdik. A pre and post-test experimental design was used to examine the effect of the comic strips strategies on students' achievement. In order to determine the effect of the comic strips implementation on the students' achievement, lessons with different degrees of implementation were compared. Pupils in a Year 3 Cerdik served as the subjects for this study. There were 30 pupils in the class; 11 girls and 19 boys. A pre-test was administered which consisted of theme-related open-ended questions. The post test showed that there was a significant improvement in the pupils' understanding of reading the narrative comprehension. Thus, it shows that the pupils gained the interest to read because they enjoyed reading using the comic strips. Data was gathered from the pre and post-test. A simple interview was also conducted with the pupils to know their responds of using comic strips in the learning process. From the data collected and the interviews done, this research found out that there was improvement in the pupils' achievement when suitable method is used in the learning process. The method used should continuously be implemented by the teacher and other teachers in the school in order to improve the pupils' reading interest in English materials.